2002
DOI: 10.1152/ajpcell.00598.2001
|View full text |Cite
|
Sign up to set email alerts
|

Potential role for Id myogenic repressors in apoptosis and attenuation of hypertrophy in muscles of aged rats

Abstract: Aging attenuates the overload-induced increase in myogenic regulatory transcription factor (MRF) expression and the extent of muscle enlargement. To identify whether mRNA levels of repressors of the MRFs are greater in overloaded muscles from aged animals, overload was achieved in plantaris muscle of aged (33 mo; n = 14) and adult (9 mo; n = 17) rats. After 14 days, plantaris muscles in the overloaded limb were ~25% and 6% larger in adult and aged rats, respectively, compared with the contralateral limb. Hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
131
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(150 citation statements)
references
References 50 publications
17
131
1
1
Order By: Relevance
“…† P<0.05 indicates significant difference from aged (26 month) group. n=4 each group It has been suggested that the mechanisms of agerelated apoptosis may differ in fast-and slow-twitch muscle types [21][22][23]. The data of the present study are consistent with this notion.…”
Section: Discussionsupporting
confidence: 91%
“…† P<0.05 indicates significant difference from aged (26 month) group. n=4 each group It has been suggested that the mechanisms of agerelated apoptosis may differ in fast-and slow-twitch muscle types [21][22][23]. The data of the present study are consistent with this notion.…”
Section: Discussionsupporting
confidence: 91%
“…This pattern was analogous to that observed for tissue levels of HNE and 3-nitrotyrosine, suggesting that the enhanced oxidative and nitrosative stress might have influenced the mitochondrial content of those proteins (Savory, Rao, Huang, Letada, and Herman 1999;Mishra, Randis, Ashraf, and ivoria-Papadopoulos 2006;Qin, Yan, Patel, Liu, and Dong 2006). However, in contrast to previous studies (Alway et al 2002;Alway et al 2003;Song et al 2006;Chung and Ng 2006), we did not detect an age-related increase in the Bax to Bcl-2 ratio. While this finding may be interpreted as a compensatory action aimed at preventing myonuclei loss, we found a concomitant increase of total mitochondrial content of Bid.…”
Section: Discussionsupporting
confidence: 81%
“…Muscle weakness in the elderly is a major health problem (27,28), and hypertrophy induced by overload is greatly attenuated in older animals (29,30). The number of myonuclei might be a limiting factor (19).…”
Section: Discussionmentioning
confidence: 99%